THE VEGETATION OF LAMBUSANGO FOREST, BUTON, INDONESIA - POWLING, ANDREW; PHILLIPS, AURORA; PRITCHETT, ROSIE; SEGAR, SIMON T.; WHEELER, REBECCA; MARDIASTUTI, ANI (Research Center for Biology, 2015)
POWLING, A., PHILLIPS, A., PRITCHETT, R., SEGAR, S. T., WHEELER, R. & MARDIASTUTI, A. 2015. The vegetation of Lambusango Forest, Buton, Indonesia. Reinwardtia 14(2): 265 - 286. - Lambusango Forest is a tropical rainforest on the island of Buton, which lies close to south east Sulawesi. The forest covers an area of about 95.000 ha, with different parts of the forest having different levels of conservation protection. It lies on rocks of both calcareous (limestone) and non-calcareous (sandstone, conglomerate, peridotite and chert) nature, which give rise to soils with varying pH values, nutrient levels and water-holding capacities. The climate is seasonal, with a dry season of three months and considerable year-to-year variability due to El Nino and La Nina events. The vegetation on the different soils and in different habitats has been studied. Over 300 species of vascular plants found in the forest and surrounding areas are listed, including trees and shrubs, herbs, climbers, epiphytes, ferns and club-mosses. Two genera, Calamus with 18 species and Ficus with 29 species, are particularly species-rich, apparently due to their ability to occupy numerous edaphic and ecological niches. Species of these two genera are also good colonists and so better able to reach Buton in the recent past than other species. The plants of the forest indicate that Buton is floristically very similar to Sulawesi, with at least 83% of the species found in the forest also being known from Sulawesi. Most of the plant families and genera present on Buton are common in SE Asia, indicating colonisation primarily from that continent. Many fewer families and genera have colonised from the Australasian continent. The conservation of plant diversity is necessary for the forest to continue as a functioning ecosystem, to the benefit of the animals of the forest and also the local people.